Outbreak of Severe Acute Respiratory Syndrome Coronavirus-2 B.1.620 Lineage in the General Hospital of Jeju Island, Republic of Korea - Ha, Young-Ran; Shin, Een-suk; Kim, Hyun-Jeong; Hyeon, Eun-Hwa; Park, Jae-Sung; Chung, Yoon-Seok (Frontiers in Microbiology, 2022)
The number of coronavirus disease (COVID-19)-positive cases has increased in Jeju Island, Republic of Korea. Identification and monitoring of new mutations in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) are extremely important to fighting the global pandemic. We report a breakout of the B.1.620 lineage harboring the E484 mutation in the virus spike protein in a general hospital on Jeju Island. A cluster of cases was detected between August 4 and September 10, 2021, involving 20 patients positive for COVID-19 of 286 individuals exposed to the virus, comprising hospital patients, staff, and caregivers. We analyzed the epidemiological characteristics and spike proteins mutation sites using Sanger sequencing and phylogenetic analysis on these 20 patients. By analyzing genomic variance, it was confirmed that 12 of the confirmed patients harbored the SARS-CoV-2 B.1.620 lineage. The breakthrough rate of infection was 2.0% in fully vaccinated individuals among these patients. Nextclade analysis revealed that these SARS-CoV-2 genomes belong to clade 20A. This is the first reported case of SARS-CoV-2 sub-lineage B.1.620, although the B.1.617.2 lineage has prevailed in August and September on Jeju, which has a geographical advantage of being an island. We reaffirm that monitoring the spread of SARS-CoV-2 variants with characteristic features is indispensable for controlling COVID-19 outbreaks.